WhatsApp and Learn English: a Study of the Effectiveness of WhatsApp in Developing Reading and Writing Skills in English - Sabri Saleh Ahmed (Hasanuddin University, 2019)
This study has examined the effectiveness of using WhatsApp, as one of mobile-assisted language learning applications, in enhancing learners’ reading and writing skills in English. Twenty EFL undergraduate students of Aden University participated in a WhatsApp English medium group with the researcher where they and the researcher chat, share news articles and comment on news articles for two months. During this period, the researcher was observing their progress and then, they were given a questionnaire to report their experience about the effectiveness of WhatsApp in developing their reading and writing skills. Findings from students’ pre-test and post-test, researcher’s observations of students’ progress and students’ responses to the questionnaire revealed that WhatsApp was very effective in developing their reading and writing skills. It helped them a lot in developing their vocabulary, grammar, reading comprehension and writing skills. The study concluded that WhatsApp English medium groups provide space for practising natural language, especially in written communication, keep students learn and practice English outside the classroom and motivate them to learn from each other. As per the findings, the study has recommended EFL teachers to use WhatsApp in their teaching of English and to motivate their students to create and join WhatsApp English medium groups as that will help them in developing students’ language proficiency through natural interaction and contextualized language use that can’t be provided by the classroom.